Sialidase NEU3 dynamically associates to different membrane domains specifically modifying their ganglioside pattern and triggering Akt phosphorylation. - Dario Bonardi; Nadia Papini; Mario Pasini; Loredana Dileo; Flavia Orizio; Eugenio Monti; Luigi Caimi; Bruno Venerando; Roberto Bresciani (PLoS ONE)
Lipid rafts are known to regulate several membrane functions such as signaling, trafficking and cellular adhesion. The local enrichment in sphingolipids and cholesterol together with the low protein content allows their separation by density gradient flotation after extraction with non-ionic detergent at low temperature. These structures are also referred to as detergent resistant membranes (DRM). Among sphingolipids, gangliosides play important roles in different biological events, including signal transduction and tumorigenesis. Sialidase NEU3 shows high enzymatic specificity toward gangliosides. Moreover, the enzyme is present both at the cell surface and in endosomal structures and cofractionates with caveolin. Although changes in the expression level of NEU3 have been correlated to different tumors, little is known about the precise distribution of the protein and its ability in modifying the ganglioside composition of DRM and non-DRM, thus regulating intracellular events. By means of inducible expression cell system we found that i) newly synthesized NEU3 is initially associated to non-DRM; ii) at steady state the protein is equally distributed between the two membrane subcompartments, i.e., DRM and non-DRM; iii) NEU3 is degraded via the proteasomal pathway; iv) the enzyme specifically modifies the ganglioside composition of the membrane areas where it resides; and v) NEU3 triggers phosphorylation of Akt, even in absence of exogenously administered EGF. Taken together our data demonstrate that NEU3 regulates the DRM ganglioside content and it can be considered as a modulator of Akt phosphorylation, further supporting the role of this enzyme in cancer and tumorigenesis.